An innovation in finite element simulation via crystal plasticity assessment of grain morphology effect on sheet metal formability. (August 2021) - Habibi, Mostafa; Darabi, Roya; Sa, Jose C de; Reis, Ana
Experimental and numerical study regarding the uniaxial tensile test and the forming limit diagram are addressed in this paper for AL2024 with the face-centered cube structure. First, representation of a grain structure can be obtained directly by mapping metallographic observations via scanning electron microscopy approach. Artificial grain microstructures produced by Voronoi Tessellation method are employed in the model using VGRAIN software. By resorting to the finite element software (ABAQUS) capabilities, the constitutive equations of the crystal plasticity were utilized and implemented as a user subroutine material UMAT code. The hardening parameters were calibrated by a trial and error approach in order to fit experimental tensile results with the simulation. Then the effect of the changing grain size, the heterogeneity factor, and the grain aspect ratio were studied for a uniaxial tensile test to emphasize the importance of the microstudy behavior of grains in material behavior. Furthermore, the polycrystal plasticity grain distribution was employed in the Nakazima test in order to obtain the forming limit diagram. The crystal plasticity-driven forming limit diagram reveals more accurate strains, taking into account the involving the micromechanical features of the grains. An innovative approach is pursued in this study to discover the necking angle, both in tensile test or Nakazima samples, showing a good agreement with the experiment results.